2012
DOI: 10.1159/000332355
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic Diagnosis of Intravascular Papillary Endothelial Hyperplasia: A Report of Two Cases and Review of Cytologic Literature

Abstract: Background: Intravascular papillary endothelial hyperplasia (IPEH), previously known as ‘Masson’s hemangioma’, is a reactive endothelial proliferation that occurs most commonly in the vessels of the head, neck, and extremities. The cytologic findings of the lesion are varied and depend on the age of the lesion. Cases: Case 1 is a 61-year-old man who presented with a swelling on the medial aspect of the forearm. The clinical diagnosis was lipoma. Cytologic smears showed spindle cells tagging onto a rich capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…The cytologic features of IPEH in the published literature show diverse morphologies, leading to frequent diagnostic error. 1 - 3 , 9 , 10 IPEH has been misdiagnosed as malignant vascular tumor, embryonal carcinoma, squamous cell carcinoma, adenoid cystic carcinoma, and giant cell tumor. Handa et al 10 suggested two types of cell populations that can assist in cytologic diagnosis of IPEH: spindle cells and round cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytologic features of IPEH in the published literature show diverse morphologies, leading to frequent diagnostic error. 1 - 3 , 9 , 10 IPEH has been misdiagnosed as malignant vascular tumor, embryonal carcinoma, squamous cell carcinoma, adenoid cystic carcinoma, and giant cell tumor. Handa et al 10 suggested two types of cell populations that can assist in cytologic diagnosis of IPEH: spindle cells and round cells.…”
Section: Discussionmentioning
confidence: 99%
“…1 - 3 , 9 , 10 IPEH has been misdiagnosed as malignant vascular tumor, embryonal carcinoma, squamous cell carcinoma, adenoid cystic carcinoma, and giant cell tumor. Handa et al 10 suggested two types of cell populations that can assist in cytologic diagnosis of IPEH: spindle cells and round cells. The spindle cells in IPEH are scattered or tagged onto a capillary network and have fine granular chromatin, prominent nucleoli, and wispy cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…US is also important for guiding fine-needle aspiration, given the fact that in some cases a diagnosis is possible with cytologic evaluation, as was observed in the present report. However, in the majority of cases, a definite diagnosis of IPEH could not be made by cytology [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Cytologic features of our case paralleled those reported in human PEH and included moderate cellularity, hemorrhagic background, pleomorphic spindle-to-round cells, hyperchromatic nuclei, and prominent nucleoli. 5,9,11,14,17,22,24 In human medicine, these findings are nonspecific and have driven various interpretations including reactive-to-malignant vascular lesions or various types of carcinoma. 5,9,11,14,17,22,24 In our 2 cases, initial cytologic findings led to the erroneous but understandable diagnostic hypothesis of FISS because cytologic findings were consistent and because FISS represents a frequent sequela of injection in cats.…”
mentioning
confidence: 99%
“…13 The diagnosis of PEH relies on the microscopic finding of a well-demarcated lesion composed of papillary projections of reactive endothelium supported by fibrovascular stalks and intimately associated with organized fibrin. 1,2,7,8,12,13 PEH represents a diagnostic challenge for pathologists because it is often misdiagnosed as malignancy and especially as angiosarcoma (AS) on both cytology 5,9,11,14,17,22,24 and histopathology. 8,12 Formerly known as "Masson tumor" from the name of the pathologist who first identified this entity, 20 PEH was originally considered a neoplastic lesion.…”
mentioning
confidence: 99%